Basal Cell Carcinoma of the Upper Lip in a Nigerian: A Case Report - A.B. Olawuyi; B.A. Onanuga; K.D. Olorunsola; O.A. Effiom; G.T. Arotiba; O. Odukoya (Nigerian Dental Journal)
A case of a 75 year old community health worker and part time farmer that presented at the Burns and Plastic Unit of the Lagos University Teaching Hospital, Lagos Nigeria was reported. The lesion commenced as a nodular mass on the upper lip which later progressed into an ulcer. The patient was managed by surgical excision and reconstruction.